Self-directed learning development for high school students and teaching issues (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The goal of this paper is to provide an implementation setting applying our method which uses the combination of cognitive capacity, personality classification and dependability criteria. The study pointed that, Differentiated teaching is a measure that needs a long and consistent implementation throughout the learning process. This measure is suitable for gifted class environments where it is necessary to allocate students into groups of equal ability to focus on fostering students' learning ability. However, this measure can also be applied to mixed groups of students with different self-study abilities by assigning students to perform collective tasks so that each student can support each other and progress throughout the course